Tattooing and pain: a look through the science lens - Kovalchuk, O I; Marchuk , O V; Pedorenko, K A (Pain medicine, 2021)
The article considers the medical aspects of tattooing, the process of tattooing and the chemical composition of the pigment. The mechanisms of pain during tattooing, its physiological and pathological aspects are described. For the first time, all possible options for analgesia during application were evaluated, and the medical aspects of each method were analyzed and described. The professional tattoos and cosmetics market of analgesics are analyzed, gels and ointments available in Ukraine are presented, the main characteristics of each of them are described. Among the registered evidence-based medicines, there are those that can be used in the process of tatooing to reduce pain. The main causes of pain when healing a tattoo and its possible management are described.